Wisconsin Institutes for Discovery -Initial Documents - Raw Data From John Wiley - Emon, Ayeshah (My University, 2008)
Includes WIDMIR pre-proposals, pre-proposal meeting reviews, correspondence, WID Design for Education and Outreach Proposal Fall 2008. Covers the time period between 2008-2009.